2017
DOI: 10.18632/oncotarget.19817
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI3K/AKT/mTOR signaling pathway as an effectively radiosensitizing strategy for treating human oral squamous cell carcinoma in vitro and in vivo

Abstract: Radiation therapy (RT) is the current standard adjuvant approach for oral squamous cell carcinoma (OSCC) patients. Radioresistance is a major contributor to radiotherapy failure. In this study, we used patient-derived cells and a radiation-resistant cell line in vitro and in vivo for two purposes: evaluate the anti-tumor effects and understand the mechanisms in the dual PI3K/mTOR signaling pathway regulation of radiosensitization. Our findings indicate that in OML1-R cells, the radioresistance phenotype is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 28 publications
4
68
0
Order By: Relevance
“…It was expected that the phosphorylation of Akt and mTOR would improve the expression of cyclin D1 since the formation of this protein can be induced through the activation of mTORC1 complex ; in addition, inhibition of the PI3K/Akt/mTOR signaling pathway promoted downregulation of cyclin D1 in oral cancer cells . However, we did not find clear overexpression of cyclin D1 when we compared the control and PDT groups.…”
Section: Discussionmentioning
confidence: 64%
“…It was expected that the phosphorylation of Akt and mTOR would improve the expression of cyclin D1 since the formation of this protein can be induced through the activation of mTORC1 complex ; in addition, inhibition of the PI3K/Akt/mTOR signaling pathway promoted downregulation of cyclin D1 in oral cancer cells . However, we did not find clear overexpression of cyclin D1 when we compared the control and PDT groups.…”
Section: Discussionmentioning
confidence: 64%
“…Drugs targeting Akt/mTOR signaling act as radiosensitizing agents because the overexpression of Akt/mTOR contributes to the malignancy and radioresistance of OSCC cells . p‐Akt, p‐mTOR, and NF‐κB levels are reported to be higher in OSCC tissues than in non‐dysplastic oral tissues .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was demonstrated that AKT is involved in response to radiation . The activation of the PI3K/AKT/mTOR signaling pathway promoted radioresistance of OSCC . So, this prompted us to think that leptin can reduce the sensitivity of OSCC cells to radiation, increasing the cell proliferation, through upregulation of EEF2 protein.…”
Section: Discussionmentioning
confidence: 99%